COVID‐19—The impact of variable and "low normal" pulse oximetry scores on Oximetry@Home services and clinical pathways: Confounding variables?. Issue 4 (23rd June 2021) - Harland, Nicholas; Greaves, Jane; Fuller, Elizabeth
Abstract: COVID‐19 Oximetry@Home services have been commissioned nationally. This allows higher‐risk patients with mild COVID‐19 symptoms to remain at home, being supplied with a Pulse Oximeter to measure their oxygen saturation (SpO2 ) two to three times daily for two weeks. Patients record their readings manually or electronically which are monitored by a clinical team. Clinical decisions, using an algorithm, are based on SpO2 readings in a narrow range with 1–2 point changes potentially affecting care. In this article, we discussed the problem that multiple factors affect SpO2 readings, and that some "normal" individuals will have "low‐normal" scores at the threshold of clinical management, without any known respiratory problem. We discuss the potential magnitude of this problem based on the associated literature and consider how this will have an impact on the use of the Oximetry@home services, potentially partially confounding their purpose; to reduce face‐to‐face medical care.